The Key Success and Strategic Role of Accrual Based Accounting Implementation - Surepno, Surepno (Bina Nusantara University, 2015)
Central Government policy to adopt accrual-based accounting system providing consequences for local governments to apply accrual accounting in the financial statements. Empirical evidence shows that the readiness of the local government in Indonesia in the process of implementation of accrual accounting is still relatively low. This study aimed to analyze the success of Semarang Government in implementing accrual accounting. This study also analyzes the offender's response to the implementation of the strategic role of accrual accounting in transparency and accountability. Furthermore, the method used in this study is a qualitative approach to perform a case study at the Department of Finance and Asset Management Area (DPKAD) Semarang by means of interviewing the key actors of implementation. The results showed that the successful implementation of accrual accounting Semarang government is supported by four main strategies, namely management commitment, regulatory development, information systems development and human resource development. Furthermore, based on the conclusions of the implementers shows that accrual accounting has a strategic role in increasing transparency and accountability through financial reporting.